Encoding of object location in a scrolling display - Yumiko Fujii; Hiromi Morita (i-Perception)
There are two main characteristics of visual information processing when viewing an image by scrolling on a small screen: viewing the image sequentially, section by section, owing to the limited visible area, and moving the image to view the desired section of the image. In this study, we investigated the effects of these characteristics on the encoding of object location. The participants were required to observe an image containing 10 objects under three viewing conditions without a time limit and to recall the location of the target object. The viewing conditions were a scrolling condition, a moving-window condition in which a fixed image was viewed by moving the window, and a no-window condition in which the entire image was viewed without a window. The results showed that although the recall accuracy did not differ among the conditions, the observation time increased in the order of scrolling, moving-window, and no-window conditions. These results indicate that in a scrolling view, the object location can be encoded with the same accuracy as that in a full view; however, more time is required for encoding. This finding suggests that viewing the image sequentially and moving the image degrade the encoding of object location.